Struktur Populasi Hama Pomacea sp. (Mesogastropoda: Ampullariidae) yang Menyerang Padi Sawah (Oryza sativa L.) Pada Ketinggian 500 Mdpl di Kabupaten Tabanan - I WAYAN KASIDIYASA; NI NENGAH DARMIATI; I MADE MEGA ADNYANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Population Structure of Pomacea sp. (Mesogastropoda: Ampullariidae) On Paddy Rice (Oryza sativa L.) At Altitude <500 Dan> 500 mdpl Tabanan Regency Research conducted from January 2018 until March 2018 in 2 different places that is in Blayu Village, Marga District and Puseh Village, Baturiti District, Tabanan Regency. The purpose of this research is to know the population structure of Pomacea sp. on rice paddy at altitude <500 and> 500 mdpl Tabanan regency. The materials used in this research are rice plants and Pomacea sp. in the field. In this research use survey method to determine population structure of Pomacea sp. on wet rice paddies conducted in Blayu Village, Marga District and Puseh Village, Baturiti District, Tabanan Regency. Observation using absolute method of observation is done directly without using tools such as traps. Observations were made 2 times a week from rice age 1 week after planting until rice grains grow. Observations made in the morning. Observation of Pomacea sp. shows the following results: Population density P. canaliculata small phase, pre adult and adult at altitude < 500 mspl (0.043, 0.044, and 0.041 individual/m2) is higher than in height > 500 mdpl (0.035, 0.042, and 0.038 individuals/m2). At an altitude of <500 mdpl population of P. canaliculata age 1 - 15 HSM, 16 -25 HSM, and 26 - 3 years after the highest hatch occurred at age 28 HST ie 7.67 snails / are, 4.20 snails / , 40 snails / acre while at height> 500 mdpl population P. canaliculata age 1 - 15 HSM, 16 -25 HSM, and 26 - 3 years after the highest hatch occurred at age 31 HST ie 6.07 snails / are, 5, 00 snails / are and 3.93 snails / are. The distribution pattern of P. canaliculata at <500 and> 500 mdpl is clumped.